New applications, new global audiences: Educators repurposing and reusing 3D virtual and immersive learning resources - Gregory, S.; Gregory, B.; Wood, D.; O'Connell, J.; Grant, S.; Hillier, M.; Butler, D.; Masters, Y.; Stokes-Thompson, F.; McDonald, M.; Nikolic, S.; Ellis, D.; et al. (2015)
There continues to be strong interest among established, experienced academic users of 3D virtual environments for their sustained educational use. Consistent with global trends, they plan to further develop and optimise existing applications, reuse skills and experiences gained to develop new applications, and to share and reuse existing virtual resources. This is against a background of varied support from institutions, colleagues, students, funding bodies and also changing understanding and awareness of virtual environments and virtual reality by the general community as a result of consumer developments such as the popularity of multi-user online role playing amongst both children and adults, and the acquisition of technologies by companies with deeply entrenched technologies. At the same time, the ongoing development and availability new multiuser virtual environment platforms, associated peripherals and virtual reality technologies promise new and exciting opportunities for educators to collaborate with researchers on a global scale, while also exploring the affordances of these technologies for enhancing the learning outcomes for an increasingly diverse and distributed student population.